Twenty‐First Century Autocrats and Their Followers: A Comparative Inquiry - Ludger Helms (Politics and Governance)
Leadership and followership have long been considered to be defining features of democratic politics. However, more recently, both conceptual redefinitions and real-world developments have put issues of leadership and followership in regimes from beyond the family of established liberal democracies center-stage. This article looks into the nature of authoritarian leadership and followership from a comparative perspective and in light of theories of democratic political leadership. As the inquiry suggests, the rise and nature of leadership activities in contemporary authoritarian regimes reflects both the turn towards more competitive types of autocracy and the aspiration of many authoritarian powerholders to be seen as democratic. At the same time, some of the most spectacular manifestations of autocratic leadership relate to democratic rather than established authoritarian regimes. While followers of autocratic leaders can control their leaders only to the extent that a regime provides mechanisms of vertical accountability, authoritarian followers, even in established autocracies, are not in all regards less important or powerful than their democratic counterparts. Many authoritarian followers do not just support autocrats, but actively attack and chase non-followers or followers of other leaders, and thus play an independent role in the legitimation or de-legitimation of leaders and regimes.